(NlEKSI^ESKIJ MINIMUM FRANCUZSKOGO QZYKA (B:s (NdLQ (BI - III (NKURSOW INSTITUTOW I FAKULXTETOW INOSTRANNYH QZYKOW (B/s - (NdE[EWICYN(B, (NmIHAIL pETROWI^s; (NkISTANOWA(B, (Nl(B.(Nf(B.s; (NmICKEWI^(B, (Nz(B.(Nw(B.s ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1972)
(NsPISOK LIT(B.: (NS(B. 181(14 (NNAZW(B.)s
Keywords: (NfRANCUZSKO(B-(NRUSSKIE SLOWARIs